Full Color Tunable Aggregation-Induced Emission Luminogen for Bioimaging Based on an Indolizine Molecular Framework - Choi, Sang Kee; Rho, Jungi; Yoon, Sang Eun; Seok, Jin Hong; Kim, Hyungi; Min, Junsik; Yoon, Woojin; Lee, Sanghee; Yun, Hoseop; Kwon, O. Pil; Kim, Jong H.; Kim, Wook; et al. (Bioconjugate Chemistry, 2020)
By taking advantage of a unique mechanism of aggregation-induced emission (AIE) phenomena, AIE luminogens (AIEgens) have been provided as a solution to overcome the limitations of conventional fluorophores bearing the feature of aggregation-caused quenching (ACQ) phenomena. Especially, AIEgens paved the way to develop fluorogenic probes ideal for fluorescent imaging in live cell conditions. Despite the high demand for discovery of new AIEgens, it is still challenging to find a versatile molecular platform to generate diverse AIEgens. Herein, we report a new colorful molecular framework, Kaleidolizine (KIz), as a molecular platform for AIEgen generation. The KIz system allows systematic tuning of the emission wavelength from 455 to 564 nm via perturbation of the electron density of substituents on the indolizine core. Increasing the water fraction of the KIz solution in the THF/water mixture induces the fluorescence intensity increase up to 120-fold. Crystal structure analysis, computational calculations, and solvatochromism studies suggest that a synergistic effect between the intramolecular charge transfer and restriction of intramolecular rotation acts as the AIE mechanism in the KIz system. Conjugation of the triphenylphosphonium moiety to KIz allows successful development of triphenylphosphonium (TPP)-KIz for real-time bioimaging of innate mitochondria in live cells, thereby revealing the potential of KIz as a versatile molecular platform to generate fluorogenic probes based on AIE phenomena. We do believe the KIz system could serve as a new, reliable, and generally applicable molecular platform to develop various AIEgens having desired photophysical properties along with an excellent signal-to-noise ratio and with experimental convenience especially for fluorogenic live cell imaging.
Keywords: Aggregation-induced emissions; Bio-imaging; Color-tunable; Fluorogenic probes; Full color; Indolizines; Live cell; Molecular frameworks; Molecular platform; Quenching phenomena; Color; Fluorescent Dyes; Indolizines; Optical Imaging; Structure-Activity Relationship